Quasi-Periodic Solutions of the Generalized KdV Equation (Analysis in Theory and Applications, 2025)
This paper concerns the existence of real analytic quasi-periodic solutionsclose to the constant function 1 of the generalized KdV equation. The proof is basedon an abstract KAM theorem for infinite dimensional Hamiltonian systems.